Pengaruh Kepatuhan Discharge Planning terhadap Gambaran Nilai Kreatinin Pasien Hemodialisa di RSUD dr.H.Chasan Boesoirie Ternate - Nunung Iriani Doa; Nursanti Anwar (Jurnal Gema Keperawatan, 2022)
Kidney failure can occur when the function of kidneys is disrupted, making them unable to discrete metabolic waste from food. Patients with terminal kidney failure undergoing hemodialysis needs to have concerns on several aspects. Dialysis or hemodialysis is blood cleaning process using dialyzer that acts as an artificial kidney to excrete the accumulated waste from the body. The waste includes substances dissolved in the blood, such as urea and potassium toxins, or their solvents, including water or blood serum. Thus, patients should comply with discharge planning to keep their condition stable as they undergo regular hemodialysis. This research examined the creatinine levels of patients with kidney failure undergoing Hemodialysis at dr. H. Chasan Boesoirie Ternate Regional Hospital.  In this quasi-experiment research, 32 purposively-selected samples were assigned into experimental group and control group. An observation checklist on discharge planning was used as the data collection instrument, which data were then analyzed in Mann whitney t test. Statistical outcomes were obtained, showing Asymp.Sig (2-tailed) value of 0.318 greater than p value 0.05. It can be inferred that there was no significant difference in the creatinine levels between experimental group and control group.